THE ANALYSIS OF SOCIAL MEDIA (TWITTER) FOR MARKETING BASED ON MARKET SEGMENTATION AT ABVANREL RUMAH MUSIK JAKARTA - Pendang, Andrina (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Companies will improve the promotion for their customers in order to supporting marketing part, and introduce what will be required to serve them extremely well in future. Promotion use Twitter to accomplish them. The objectives of this research are to partially and simultaneously. This research is a causal type of research where it investigate the influence of social media on promotion. Using multiple regression model to answer the research problem. The population observed is Followers of Music House Twitter Account with sample as many as 100 respondents. The hypothesis testing, this research conduct a conclusion of there is a significant influence of number of followers and length of membership and partially on music house promotion. This study reveals that twitter is a new media that made the consumer has a strong influence factor in order to buy a product, when consumer go for purchasing, they prefer to purchase a product with a well know about the information of product its self, good posting and detail information of music house account. Keywords: social media marketing, market segmentation.